Utility of micro-TESE in the most severe cases of non-obstructive azoospermia - Göran Westlander (Upsala Journal of Medical Sciences, 2020)
The use of intracytoplasmic sperm injection (ICSI) has been a major breakthrough in the treatment of male infertility. Even patients with non-obstructive azoospermia (NOA) may benefit from the ICSI technique to father a child as long as spermatogenesis is present. There are several techniques to recover testicular sperm in patients with NOA. However, retrieval of spermatozoa is unfortunately still only successful in a subset of patients with NOA, and the most superior sperm retrieval method is still under debate. A more recent technique, microdissection testicular sperm extraction (MD-TESE) with an operative microscope collecting larger and more opaque seminiferous tubules, is a non-blind sperm retrieval technique with theoretical benefits. The MD-TESE procedure seems to be feasible, effective, and safe in NOA patients but also more technically demanding and time-consuming compared with conventional blind techniques. In the present report, we describe our clinical experience and results from our first 159 MD-TESE procedures. The probability to retrieve sperm with the MD-TESE technique is high in NOA cases where earlier sperm retrieval with blind methods such as needle aspiration, percutaneous needle biopsy, or conventional TESE has failed.